Naturalism in mathematics - Maddy, Penelope (Clarendon Press ; Oxford University Press, 1997)
Set theory has rendered the notion of self-evident truths to be obsolete in mathematics. Penelope Maddy examines this dilemma using the minimum of technical jargon. Set theory is explained in a manner that can be understood by non-mathematicians.